2012
DOI: 10.1590/s0103-21002012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Adesão às precauções-padrão de profissionais de enfermagem de um hospital universitário

Abstract: Objective: To describe and compare the scores of adherence to standard precautions (PP) by nursing professionals who worked in inpatient units of a university hospital in the state of São Paulo (Brazil). Methods: This was a transversal, quantitative, comparative study, using a psychometric scale to measure adherence to PP, developed by Gershon et al., (1995), translated and validated by Brevidelli and Cianciarullo (2009), that was conducted between September 1, 2009 and March 31, 2010, with 256 nursing profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
2
1
0
14
Order By: Relevance
“…Since health workers are exposed in the workplace to various microorganisms, it is necessary for them to be vaccinated against those pathogens for which there are available vaccines. 5,12,17,18 Most nursing professors surveyed in this study (80%) reported complete vaccination for hepatitis B, as mentioned in other studies. 5,12,17 Analysis of the data in relation to anti-HBs exams by professors found that 77.1% have done it, and 71.4% said they were immunized for hepatitis B.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Since health workers are exposed in the workplace to various microorganisms, it is necessary for them to be vaccinated against those pathogens for which there are available vaccines. 5,12,17,18 Most nursing professors surveyed in this study (80%) reported complete vaccination for hepatitis B, as mentioned in other studies. 5,12,17 Analysis of the data in relation to anti-HBs exams by professors found that 77.1% have done it, and 71.4% said they were immunized for hepatitis B.…”
Section: Resultssupporting
confidence: 71%
“…5,12,17,18 Most nursing professors surveyed in this study (80%) reported complete vaccination for hepatitis B, as mentioned in other studies. 5,12,17 Analysis of the data in relation to anti-HBs exams by professors found that 77.1% have done it, and 71.4% said they were immunized for hepatitis B. These data differs from a study, in which 86.4 % of nurses did not perform the anti-HBs serologic testing due to factors such as ignorance of its importance and lack of time.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…O trabalho do enfermeiro no cuidado de pessoas com lesão -Dinâmica do trabalho 10-11, [25][26][32][33]35,[39][40] -Estabelecimento de protocolos institucionais 23,25,[27][28]31,34,36,39 -Equipamentos e insumos 19-20,23,28-29-40 -Necessidades das pessoas com lesão 8,11-12, 23,25,28,31,[34][35][36][37][39][40] Consequências da exposição ao risco ocupacional na realização do cuidado -Necessidades de cuidado profissional em consonância com os riscos de exposição 1,8-38-40 -Acidente de trabalho 9,11,13-14,19,21,31,40 -Adoecimento no trabalho 11,16,19,26,28,[35][36]40 Atuação livre de riscos -Conhecimento 9-10,13, [23][24][25][26][33][34][35][36]40 -Precauções universais 8,11,20,25,28,30,35,…”
Section: Categorias Temáticas Subcategorias Temáticasunclassified
“…Igualmente, visa obter elementos para o enfermeiro intervir com vistas à atuação livre de riscos, haja vista as preocupações com as condições de trabalho, o desgaste físico e mental, os acidentes de trabalho e o adoecimento enquanto cuida, observados os limites e parâmetros da legislação vigente O perfil dos artigos analisados apresentou 19 publicações no idioma inglês 8-23, [25][26]38 e 14 no idioma português. 24,[27][28][29][30][31][32][33][34][35][36][37][39][40] Quanto ao tipo de pesquisa empregada nas publicações disponibilizadas na pesquisa destacamse a revisão sistemática, 8 a pesquisa quantitativa, 10,12-13,16-21, [23][24][25][28][29]31,33,[36][37] a pesquisa mista quanti-qualitativa 35 , o relato de experiência, 39 a pesquisa documental, 9,14,26,32,34 a pesquisa qualitativa 1,15,27,40 e a revisão integrativa. 22,30 32 Riscos velados − Primeira consulta de enfermagem após seis meses a um ano do início da ferida 33 Riscos velados − Excreções / Secreções / Imprevisibilidade 34 Todos* − Conhecimento / Riscos químicos, biológicos e de acidentes são temas evidenciados pela literatura 35 Todos* − Conhecimento / Riscos ergonômicos e físicos são pouco explorados na literatura dentre os demais riscos 36 Todos* − Contato com fluidos / Ausência de EPI / Resistência no uso do EPI 37 Biológico − Exposição a material biológico 38 Ergonômico − Vício postural 39 Todos* Desconhecimento do risco…”
Section: Introductionunclassified